Squirt Magert : the fraidy frog an "I-like-myself" book - Jimenez, Gidget R. (Tahanan Books for Young Readers, 2000)
"A dog's bark sends Squirt Magert hiding in the bushes. Too late! "Are you as fast as a rocket?" laughs the Boy, stuffing the little frog down his pocket. Poor Squirt is both doomed and groomed to run in the Boy's frog race. As the frog pack tumbles headlong downhill, Squirt braces himself for the unknown adventure that will change his life. The "I-Like-Myself" books are designed to help parents build a child's self-confidence. Using big, bold text and appealing illustrations, these books are an irresistible invitation to youngsters to read on their own."